Development Of An Active Suspension System To Prevent Passenger Cars Rollover (Latakia University Journal -Engineering Sciences Series, 2024)
Rollover is one of the most dangerous maneuvers that a vehicle may undergo at driving , and the main cause of most traffic accidents deaths . Therefore, this study  presents  a developed model of Double A-Arms Suspension System , designed specifically to prevent the rollover of passenger cars during critical cornering maneuvers . The developed suspension system distinguishes by its ability to control of its roll center position , by controlling the inclination angles of the upper transverse arms , and  its ability to provide an increase in the vehicle  track width , during the control of   roll center  position .A model of the  developed suspension system was built within the MATLAB-Multibody modeling environment  . All parameters of this model were set to be equivalent to the parameters of the “Double Wishbone Suspension” reference model, built for a traditional Double A-arms Suspension System in the same previous environment, and stored within the MATLAB example library. The reference and developed models were then tested under the same critical cornering maneuver conditions .The developed  model showed an ability to avoid rollover , unlike the reference  model .  The developed  model  also retained  its ability to provide a good level of vibration dampening .